PENGARUH FIRMSIZE, DEBT TO EQUITY (DER), DAN AKTIVITAS (TATO) TERHADAP PROFITABILITAS PERUSAHAAN SUBSEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2017 - Mesrawati, .; Sihombing, Carlos; Samjaya, Ervina (GOING CONCERN : JURNAL RISET AKUNTANSI, 2019)
This purpose this researchÂ  to get tasted on the effect of Firm Size, Debt to Equity, and Activity on Profitability in the property and real estate sub-sector companies listed on the Indonesia Stock Exchange in 2013-2017. The research sample consisted of 29 companies selected through Purposive sampling techniques. The data used in this study is secondary data, by collecting data or information in the form of financial statements needed from idx. The analytical method used is multiple regression analysis and assumption test. The research subjects were property and real estate companies listed on the Indonesia Stock Exchange for the period 2013-2017. From the results of the discussion showed that partially with the t test, Firm Size variable, Debt to Equity and Activity had an effect on Profitability. Simultaneous results of independent variables; Firm Size, Debt to Equity and Activities with the F test, together have an effect on Profitability. The coefficient of determination shows that independent variables are able to influence the dependent variable.Keywords: firmsize,debt to equity ,aktivitas.